2009
DOI: 10.1080/09546630902936760
|View full text |Cite
|
Sign up to set email alerts
|

A Medicare cost comparison of minor cutaneous procedures by surgical setting

Abstract: Regulations that discourage office-based surgery could significantly increase medical care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Medicare data have been used previously to determine the systemic costs of treating keratinocyte cancers in Australia, although this is the first study to determine costs per patient, and across different clinical settings. A study based on US Medicare data found that the average cost for each skin cancer treated in hospital was five times more than the costs for treating skin cancers in private clinical rooms (US$645 vs US$128) . While we found similarly that hospital admissions result in higher costs, we found smaller relative differences between the clinical settings.…”
Section: Discussioncontrasting
confidence: 63%
“…Medicare data have been used previously to determine the systemic costs of treating keratinocyte cancers in Australia, although this is the first study to determine costs per patient, and across different clinical settings. A study based on US Medicare data found that the average cost for each skin cancer treated in hospital was five times more than the costs for treating skin cancers in private clinical rooms (US$645 vs US$128) . While we found similarly that hospital admissions result in higher costs, we found smaller relative differences between the clinical settings.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition to safety, outpatient surgery under local anesthesia avoids the additional cost of an operating facility, administration of anesthesia, and postoperative recovery 15,49,50 . Although cost‐effectiveness was not a factor included in this study, the cost‐effectiveness of outpatient MMS has been well established 15,20–22,49,50 …”
Section: Discussionmentioning
confidence: 99%
“…3,4 The unadjusted mean cost of treating NMSC has been found to differ by 200% to 500% among primary care physicians, dermatologists, otolaryngologists, and plastic surgeons. 3 Additionally, given that all specialists are reimbursed the same amount per procedure code, a recent paper by Marks et al 5 has suggested that dermatologists should be considered the most cost-effective specialty treating NMSC as they perform almost all of their procedures in the office (compared to plastic surgeons and otolaryngologists, who treat NMSC patients in hospital or ambulatory surgical center settings). Marks et al 5 concluded that more severe NMSC cases were unjustifiably treated in more costly settings such as hospitals or ambulatory centers despite finding higher mean Charlson Comorbidity Index scores of 2.03, 2.65, and 3.02 for NMSC patients treated in an office, ambulatory surgical center, or a hospital, respectively.…”
mentioning
confidence: 98%
“…3 Additionally, given that all specialists are reimbursed the same amount per procedure code, a recent paper by Marks et al 5 has suggested that dermatologists should be considered the most cost-effective specialty treating NMSC as they perform almost all of their procedures in the office (compared to plastic surgeons and otolaryngologists, who treat NMSC patients in hospital or ambulatory surgical center settings). Marks et al 5 concluded that more severe NMSC cases were unjustifiably treated in more costly settings such as hospitals or ambulatory centers despite finding higher mean Charlson Comorbidity Index scores of 2.03, 2.65, and 3.02 for NMSC patients treated in an office, ambulatory surgical center, or a hospital, respectively. Interpretation of the results reported by the aforementioned studies is limited as they summed costs of the entire episode over all specialties involved and did not control for confounding factors such as patient demographics or disease severity that may require more specialized, and thus more costly, care.…”
mentioning
confidence: 98%